Aktivitas Imunostimulan Daun Elaeocarpus grandiflorus terhadap Jumlah Leukosit dan Histologi Limpa Tikus yang Diinduksi SDMD - Nugrahaningsih WH; Eny Susanti; Mutiara Diah Nisa (Universitas Negeri Semarang, 2023)
The aim of this study was to examine the activity of various doses of E. grandiflorus leaf extract on the number of leukocytes, neutrophils, lymphocytes and histological features of the spleen in male rats induced by sheep red blood cells (SRBC). 25 rats were divided into 5 groups. The negative control was given 1% Na.CMC, the positive control was given an immunostimulant drug, and the three treatment groups received doses of 100mg/kg, 200mg/kg, and 400mg/kg. Oral treatment for 7 days. SRBC was injection on the 8th day. On the 13th day termination was carried out. The average leukocyte results were 6.54x103 cells/μL (K−), 6.22x103 cells/μL (K+), 10.8x103 cells/μL (P1), 10.98x103 cells/μL (P2), and 11.2x103 cells/μL (P3). The results of the number of lymphocytes have a percentage of 44% (KN), 50% (KP), 45% (P1), 52% (P2), and 50% (P3). The neutrophil count results were 44.3% (K−), 35% (K+), 37.4% (P1), 30.4% (P2), and 31.9% (P3). The results of the white pulp diameter measurements had an average of 418.0 µm (K-), 440.8 µm (K+), 471.2 µm (P1), 489.8 µm (P2), and 422.0 µm (P3). The averages obtained from germinal center measurements were as follows 252.1 (K-), 225.8 (K+), 212.8 (P1), 216.3 (P2), and 198.4 (P3). ANOVA showed no significant white pulp diameter difference (p > 0.05). In conclusion, the immunostimulatory activity test on rejasa extract on the parameters of leukocytes, neutrophils and lymphocytes had a normal average number. Meanwhile, administration of rejasa extract to the spleen histology have no significant immunostimulating activity.